Maternal mortality in St. Petersburg, Russian Federation - Gurina Natalia A; Vangen Siri; Forsén Lisa; Sundby Johanne (The World Health Organization, 2006)
OBJECTIVE: To study the levels and causes of maternal mortality in St. Petersburg, Russian Federation. METHODS: We collected data about all pregnancy-related deaths in St. Petersburg over the period 1992-2003 using several sources of information. An independent research group reviewed and classified all cases according to ICD-10 and the Confidential Enquiries into Maternal Deaths in the United Kingdom. We tested trends of overall and cause specific ratios (deaths per 100 000 births) for four 3-year intervals using the chisuperscript two test. FINDINGS: The maternal mortality ratio for the study period was 43 per 100 000 live births. A sharp decline of direct obstetric deaths was observed from the first to fourth 3-year interval (49.8 for 1992-94 versus 18.5 for 2001-03). Sepsis and haemorrhage were the main causes of direct obstetric deaths. Among the total deaths from sepsis, 63.8% were due to abortion. Death ratios from sepsis declined significantly from the first to second study interval. In the last study interval (2001-03), 50% of deaths due to haemorrhage were secondary to ectopic pregnancies. The death ratio from thromboembolism remained low (2.9%) and stable throughout the study period. Among indirect obstetric deaths a non-significant decrease was observed for deaths from cardiac disease. Death ratios from infectious causes and suicides increased over the study period. CONCLUSIONS: Maternal mortality levels in St. Petersburg still exceed European levels by a factor of five. Improved management of abortion, emergency care for sepsis and haemorrhage, and better identification and control of infectious diseases in pregnancy, are needed.